The risk to cultural identity – Narrative of Mrs Takurine Mahesh Singh (1872–1959) - Archary, Kogielam (HTS teologiese studies, 2021)
The article purports to examine the risk to cultural identity amongst an Indian community in South Africa using a single case study methodology. A case study approach was followed, using the qualitative research methodology, whereby not only the how (observation), but also adding focus on the thoughts, feelings, perceptions, experiences and motivations that people have underlie their behaviour. The year 1960 marked the 100th anniversary of the arrival of the Indians to the Colony of Natal, hence the study considers the period 1895 to 1960. Identifying with a particular culture allows members of that community to experience feelings of belonging and security. Moving across continents, Indian indentured sugar plantation labourers came to the Colony of Natal from 1860 until 1911 bringing with them their cultural identity. The risk to cultural identity is a significant contributor to an individual’s well-being. Cultural identity may be viewed as a sense of belonging based on one’s ancestry, rituals, religion, traditions, values and even language. When they were transported during the concurrent time of colonisation and indenture, they became displaced and thus an emotional threat to their well-being, belonging and security was created and simultaneously experienced. This threat compromised their cultural identity. This risk to cultural identity is investigated in the narrative of an Indian female national matriarch, Mrs Takurine Mahesh Singh who arrived in the Colony in 1895 and passed away in 1959. A risk to cultural identity existed, but the Indian community in South Africa did not experience deculturalisation. They were able to practise their ancestral culture without losing their identity. This is one of the findings and it concludes the abstract.Contribution: The study of identity, identity diffusion, identity loss is a very important aspect to study, especially for displaced communities who suffer not only alienation from their mother country, but also losing contact and cultures as a result of displacement. This article provides insight on the risk to cultural identity in Natal between 1895 and 1960. In terms of the findings, cultural identity is an important contributor to well-being. Identifying with a particular culture gave the matriarch a feeling of belonging and security. It also provides access to social and other networks which provide support and shared strength, values and aspirations. Although a product of oral history, for this research, the article could not be supported by other historical materials in an attempt at balancing the views as scholars have not explored the widowed Indian nationals who have remained in the Colony after indenture. This article should not be viewed simplistically as a retelling of Mrs Singh’s life story, but rather a narrative based on reflective memories that pieced together her departure from India under the political system of indenture, living and surviving as a widow under harsh laws and having multiple identities. The narrative oral history approach combined with a qualitative research methodology does not focus on analysis and interpretation but rather brings to the fore, the opportunity for further exploratory studies where the question ‘why’ will be answered.